A centralized IoT-based process cycle time monitoring system for line balancing study - Sadun, Amirul Syafiq; Chulakit, Saranjuu; Jalaludin, Nor Anija; Jalani, Jamaludin; Ahmad, Suziana; Md Hanapi, Muhammad Haziq; Sabarudin, Nur Aminah (Semarak Ilmu Publishing, 2023)
This study proposes a Centralized IoT-based Process Cycle Time Monitoring System (CTMS) to improve the efficiency and accuracy of line balancing studies in a production line with a conveyor system. The traditional approach of measuring cycle time, typically done by manual observation and recording, can be prone to errors due to human factors such as fatigue or inaccuracies in manual recording. The proposed CTMS utilizes a combination of cutting-edge technologies such as a cloud database, android application, LABVIEW GUI, analogue infrared (IR) sensors, and appropriate controllers to improve the reliability of cycle time measurements. The system continuously monitors the production line and provides real-time data on cycle time, downtime, and other relevant metrics, allowing production engineers to quickly identify bottlenecks and areas for improvement. The results of the study demonstrate the potential of the CTMS to be applied and expanded to actual production lines with conveyor systems, providing a valuable tool for production engineers to develop strategies to reduce cycle time and ensure it is kept in check. The proposed CTMS is expected to have a positive impact on the efficiency and profitability of the production line by reducing downtime and increasing productivity.